How do global banks scramble for liquidity? Evidence from the asset-backed commercial paper freeze of 2007 - Viral V. Acharya; Gara Afonso; Anna Kovner (Federal Reserve Bank of New York, 2013)
In August of 2007, banks faced a freeze in funding liquidity from the asset-backed commercial paper (ABCP) market. We investigate how banks scrambled for liquidity in response to this freeze and its implications for corporate borrowing. Commercial banks in the United States raised deposits and took advances from Federal Home Loan Banks (FHLBs). In contrast, foreign banks - with limited access to the deposit market and FHLB advances - lent less in the overnight interbank market and borrowed more from the Federal Reserve's Term Auction Facility (TAF) auctions. Relative to before the ABCP freeze and relative to their non-U.S. dollar lending, foreign banks with ABCP exposure charged higher interest rates to corporations for syndicated loan packages denominated in dollars. The results point to a funding risk in global banking, manifesting as currency shortages for banks engaged in maturity transformation in foreign countries.
Keywords: G01; G21; G38; 330; funding risk and liquidity; global banking; ABCP freeze